Response of Reinforced Concrete Frames with Infilled Panels under Earthquake Excitation - Singh, Harpal (My University, 2007)
The studies reported here in focus on the three-dimensional linear elastic and nonlinear inelastic seismic response of reinforced concrete frame structures with non integral masonry infill panels. The infills provide significant stiffness and strength to the framing structure characterised by its interaction with the frame. Under the load, the mortar may crack causing sliding and separation at the interface between the infill and the frame. Further the infill may get cracked and /or crushed which change its structural behaviour and may render the infill ineffective leaving the bare frame to take all the load which may lead to the failure of the framing system itself. A mathematical model for the inelastic static anddynamic analyses of the frame systems has been presented to simulate the above behaviour. In the investigation , eight-noded panel elements ,six-noded interface elements and three-noded frame elements have been used to edealise the infill panel, frame-infill interface and the bounding frame ,respectively. For the infill smeared crack model has been adopted, whilefor the frame, elasto-plastic behaviour with associated flow rute has been assumed. At the interface between the frame and the infill the tangential stress-strain relationship has been assumed to be elastic perfectly plastic. Based on the above model a computer proram has beendeveloped for the elastic and inelastic static and dynamic analyses of three-dimensioal infilled reinforced concrete frame buildings.The model predicts the sequence of formation of plastic things in the frame and cracks in the infill, and the entire time history response of the infill frame systems to the earthquake excitation. The investigation has shown that the stiffness andstrength of an infilled frame systems are extremely under estimated on the exclusion of the effect of infill from the analysis. The seismic response of both the two and three dimensional infilled frame systems has been discussed in detail. The computer program has successfully simulated the post earthquake failure/damage analyses of infilled reinforced concrete framed buildings. Asimplified model has been proposed for the analysis of the real sized infilled concrete frame sytems. In the simplified model the infill has been idealised as a billnear diagonal member acting both as a strut and a tia. The model provides reasonably close results to the reported experimentals results.
Keywords: Reinforced Concrete Structures; Earthquake Engineering; Frames; Reinforced Concrete Frames